Accidental Formation of Eutectics during Crystal Engineering of Lamotrigine with Solubility Advantage and Drug Release Efficiency (Asian Journal of Pharmaceutics (AJP), 2021)
Objective: Lamotrigine (LMG) is the Biopharmaceutical Classification System Class-II drug with hurdle in drugrelease and dissolution efficiency due to poor water solubility. The present investigation was aimed to improvethe solubility and dissolution of LMG by crystal engineering by formation of cocrystals but which accidentlyturn toward eutectics formation. Methods: LMG was subjected to neat grinding with different Cocrystal Formers(CCF) to develop multicomponent crystalline system. The prepared multicomponent system was analyzed byDifferential Scanning Calorimetry, Raman spectroscopy, and Powder X-ray Diffraction reveals the formationof multicomponent system. Improved dissolution was interpreted by comparative drug release study of tabletformulation of unprocessed drug and eutectics. Results: There was unplanned formation of eutectics of LMGAscorbicacid (LMG-AA) that was observed with improved drug solubility. LMG-AA eutectics showedenhanced solubility (651.61 ± 1.02 μg/ml) in comparison with pure drug (161.46 ± 0.86 μg/ml) and all remainingmulticomponent systems formed with other CCF’s. The LMG-AA eutectics showed comparatively better drugrelease than pure LMG tablet. LMG eutectics also showed significant improvement in flow properties andcompressibility as compared to pure drug. Conclusion: Multicomponent LMG-AA eutectics although formed inunplanned way they effectively enhances the solubility of LMG serving the main purpose of the research work. Itcan be utilized efficiently for drug delivery due to its improved dissolution and better drug release.